2014
DOI: 10.1080/10410236.2013.841532
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Perceived Contradictions in End-of-Life Communication: Toward a Self-Report Measurement Scale

Abstract: Communication is undoubtedly a critical element of competent end-of-life care. However, physicians commonly lack communication skills in this particular care context. Theoretically grounded, evidence-based guidelines are needed to enhance physicians' communication with patients and their families in this important time of their lives. To address this need, this study tests and validates a Contradictions in End-of-Life Communication (CEOLC) scale, which disentangles the relational contradictions physicians comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Indeed, patients and their families are often not satisfied with the care received at the end of life in the ICU and communication with caregivers is the least accomplished factor in quality of care. 36 Recently published studies have confirmed the need for an evidence-based approach to communication in EOL, 37 but highlight the lack of empirical data needed to support theoretical frameworks that can clarify the role of communication in end-of-life care.…”
Section: Skills and Knowledge In End-of-life Carementioning
confidence: 97%
“…Indeed, patients and their families are often not satisfied with the care received at the end of life in the ICU and communication with caregivers is the least accomplished factor in quality of care. 36 Recently published studies have confirmed the need for an evidence-based approach to communication in EOL, 37 but highlight the lack of empirical data needed to support theoretical frameworks that can clarify the role of communication in end-of-life care.…”
Section: Skills and Knowledge In End-of-life Carementioning
confidence: 97%
“…14,29 Shefer et al 26 explored the views and attitudes of healthcare: self-critical (biomedical), medical critical, traditional and integrating; highlighting the different aspects to consider when trying to engage people and the relative importance of healthcare to each individual. These points of view can vary across a variety of topics: medications seen as both harmful and helpful, 30 assisted dying and euthanasia, 19,31,32 and what counts as an illness within the society. 26 This may lead to the development of a lack of understanding of their own health,…”
Section: Multicultural Attitude To Healthmentioning
confidence: 99%
“…43,[49][50][51] The make-up of the population of medical specialties varies, with physiotherapists being divided by gender and so the male domination of sports and manual therapy, 52 and that there is a statistically significant difference between the characteristics of a physician in the surgical speciality in comparison to one in a non-surgical specialty, with regards to gender and political identity. 53 Physician attitude is also different with regards to their views on assisted dying and dementia, 19 truthfulness to the patient and their family 31 and their perceptions of end of life care. 37 The performance of medical students has been shown to be dependent on their ethnicity and the culture that they are in, with research revealing that in the UK, those who are non-White are more likely to have a lower achievement, although networking factors had a greater impact on grades than ethnicity.…”
Section: Cultural Diversity Of Healthcare Professionalsmentioning
confidence: 99%